Male And Female Differences Of Writing Anxiety - Kenya Ariartha; Rika Riwayatiningsih; Yunik Susanti (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
This research aim to determine differences of writing anxiety and the cause factors behind the anxiety suffered by male and female students. The study is a quantitative study and adapted two types of questionnaires to collect the required data, (Second Language Writing Anxiety Inventory) by Cheng (2004) and CSLWAI (Cause of Second Language Writing Anxiety Inventory) by Rezaei and Jafari (2014). The subject of this study are 30 male students and 33 female students. The result showed that male students suffered cognitive anxiety, avoidance behavior anxiety and somatic anxiety. Meanwhile, female students suffered somatic anxiety and cognitive anxiety. Male students factors of writing anxiety are linguistic difficulties followed with writing techniques while female students only had writing techniques ad factors affecting their writing anxiety. In conclusion, male students had worse writing anxiety than female students. Therefore, develop teaching and learning method with the awareness of male and female students’ writing anxiety is highly recommended in order for students to be able to learn English language effectively.